EXPERIMENTAL STUDY OF FORCED, NATURAL, AND COMBINED CONVECTION IN SUBCHANNELS OF VERTICAL ROD BUNDLE WITH A SQUARE ARRAY - SUPRIYADI (NIM: 24907007); Pembimbing 1 : Dr. Ir. Nathanael P.Tandian; Pembimbing 2 : Dr. Ir. , JOKO
Forced, natural, and combined convection in vertical rod bundles are important heat transfer mechanisms and widely used in many engineering applications. Examples of such applications are design and operation of heat exchanger and nuclear reactor core. Therefore, heat transfer correlations are important to be developed for forced, natural, and combined convection regimes in vertical rod bundles. Numerous studies of heat transfer in rod bundles have been conducted, but there is almost no correlation in scope of thermally or hydrodynamically developing flows. Experimental study on laminar-forced, natural, and combined convection has been done in this research in a square configured of cylinders having P/D ratios of 1.16. During the experiment the flow of all convection regimes is still thermally and hydrodynamically developing. The hydraulic diameter of the sub-channel is used as characteristic length. In the experiment, the forced convection regime Reynolds number varies from 380 to 1660 and its Graetz number varies from 164 to 2844. The natural convection regime Rayleigh number varies from 1.96 109 x to 2.70 x 109. In combined convection Richardson number varies from 14 to 621.